Frequency of Urinary Incontinence and its Risk Factors among Pregnant Women - Javeria Khan, Maida Mushtaq, Shazia Rafiq, Sobia Zia, Siddiqa Qamar, Myra Saeed, Sajjid Iqbal, Sadia Sukhera, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The frequency of urinary incontinence and its risk factors among pregnant women in second and third trimester of Jinnah Hospital and Lady Willingdon Hospital using ICIQ-UI-SF. Study design: This is a cross-sectional observational study. Place and duration: 350 subjects were included in study by Non-probability/purposive sampling technique from Jinnah Hospital, Lahore and Lady Willingdon Hospital, Lahore and completed in 6 months. Methodology: International Consultation on Incontinence questionnaire- Urinary Incontinence- Short Form (ICIQ-UI-SF) was used to evaluate subjects to UI severity. Data was analyzed using SPSS version 21. Results: According to ICIQ-UI-SF questionnaire, out of 350 respondents, 11(3.1%) respondents showed slight symptom severity, 44(12.6%) respondents showed moderate symptom severity, 32(9.1%) respondents showed severe symptom severity and 263(75.1%) showed no symptoms at all. On a scale of 10, urinary incontinence affected the quality of life of pregnant females by 6. There was a statistical significance between ICIQ-UI-SF score and parity and number of previous vaginal deliveries (p=.011 and p=.000 respectively). Conclusion: In this study it is concluded that considerate number of respondents had symptoms of Urinary Incontinence irrespective of their trimester of pregnancy. There was no association found between disease severity and age of the respondents. Trimester of pregnancy did not have any statistical significance with the symptom’s severity, but it was found to have a statistical significance with parity and the number of previous vaginal deliveries. Key words: iCIQ-UI-SF, Pregnancy, Urinary Incontinence